STUDI KUALITATIF: KETERKAITAN AUDIT TENURE DENGAN KUALITAS AUDIT - Panggabean, Maulina; Islamudin, Ardhi (Program Studi Akuntansi Universitas Flores, 2026)
This study aims to explore the effect of Audit tenure on audit quality, which is the length of the working relationship between the auditor and the client with the resulting audit quality. This study uses a descriptive qualitative approach, data obtained through in-depth interviews with senior audits at the public accounting firm (KAP) X Surabaya. This study explores the views and experiences of practitioners regarding the impact of the length of the auditor-client cooperation period on independence, objectivity, and accuracy of audit implementation. The results of the study indicate that Audit tenure affects audit quality. The longer the audit assignment period, the deeper the auditor's knowledge of the operations and business characteristics of the company being audited, but the longer the audit assignment also risks reducing auditor independence. To overcome this risk, KAP X implements an audit team rotation policy, conducts inspections and reviews to maintain audit quality. This study provides new insights into the management of Audit tenure at KAP X and can be a reference for other KAPs in managing relationships with clients. Therefore, the balance of Audit tenure duration is an important factor in maintaining audit quality. These findings provide practical insights for audit firms and regulators in formulating auditor rotation policies.